Dukungan Sosial Rekan Kerja pada Mahasiswa yang Kuliah Sambil Bekerja: Studi Kasus Pada 3 Mahasiswa FISIP Universitas Jember - Mahfudz Sidiq; Hayatun Nufus (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
This study explores social support strategies provided by colleagues to students of the Faculty of Social and Political Sciences, University of Jember, who work while studying. Student-workers face challenges such as academic pressure, limited time, fatigue, and role conflict. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation. The findings show that colleagues offer various forms of support, including emotional, instrumental, informational, appraisal, and network support. These strategies help student-workers manage dual-role burdens and maintain balance between academic and work responsibilities.